Epigenetic regulation of human SOX3 gene expression during early phases of neural differentiation of NT2/D1 cells. - Vladanka Topalovic; Aleksandar Krstic; Marija Schwirtlich; Diletta Dolfini; Roberto Mantovani; Milena Stevanovic; Marija Mojsin (PLoS ONE)
Sox3/SOX3 is one of the earliest neural markers in vertebrates. Together with the Sox1/SOX1 and Sox2/SOX2 genes it is implicated in the regulation of stem cell identity. In the present study, we performed the first analysis of epigenetic mechanisms (DNA methylation and histone marks) involved in the regulation of the human SOX3 gene expression during RA-induced neural differentiation of NT2/D1 cells. We show that the promoter of the human SOX3 gene is extremely hypomethylated both in undifferentiated NT2/D1 cells and during the early phases of RA-induced neural differentiation. By employing chromatin immunoprecipitation, we analyze several histone modifications across different regions of the SOX3 gene and their dynamics following initiation of differentiation. In the same timeframe we investigate profiles of selected histone marks on the promoters of human SOX1 and SOX2 genes. We demonstrate differences in histone signatures of SOX1, SOX2 and SOX3 genes. Considering the importance of SOXB1 genes in the process of neural differentiation, the present study contributes to a better understanding of epigenetic mechanisms implicated in the regulation of pluripotency maintenance and commitment towards the neural lineage.